Effect of Ethanol Extract from Herbal Consortium for Pytirosporum ovale Inhibition - Lilis Sugiarti; Dian Arsanti Palupi; Indah Febriana (JURNAL SAINS NATURAL, 2022)
Dandruff is a skin disease caused by the fungus Pytirosporum ovale. The use of chemical compounds for dandruff is very limited and can cause side effects, such as toxicity to the eyes and hair becoming too dry. The consortium of herbal plants was hope had greater inhibitory activity than the single plants. The purpose of this study was to determine the antifungal effectiveness of a consortium of herbs (soursop leaves, basil leaves, bay leaves and green betel leaves) in a 1:1:1:1 ratio against Pytirosporum ovale. Extraction method using maceration method and 70% ethanol solvent. The extract of the herbal consortium was made in series with concentrations of 10, 25, 40, 55 and 70%, a negative control and a positive control by disc diffusion method. Data analysis using Post Hoc LSD test, correlation, and linear regression. The results showed that all concentrations of extract of the herbal consortium could inhibit the activity of the fungus Pytirosporum ovale. The minimum inhibitory concentration was at a concentration of 10% with a diameter of 7.33 mm while the optimum inhibitory at a concentration of 70% with a diameter of 15.55 mm. The inhibition zone diameter in positive control of 24.66 mm. The results of the correlation test show a very strong and unidirectional relationship. The results of the linear regression test obtained the value of y=0.138x+5.889. The diameter of the fungal inhibition zone was influenced by the extract concentration of 99.99% (r2=0.9999), the remaining 0.01% was influenced by other factors such as temperature, radiation, light, humidity, pH and others. The ethanol extract of the herbal consortium was not effective in inhibiting the growth of the fungus Pytirosporum ovale when compared to positive control.Keywords: Herbal consortium; Ethanol extract; Antifungal; MIC; Pytirosporum ovaleABSTRAKEfektivitas Ekstrak Etanol Konsorsium Herbal terhadap Pytirosporum ovaleKetombe merupakan penyakit kulit yang disebabkan adanya jamur Pytirosporum ovale. Konsorsium herbal diharapkan mempunyai potensi antijamur yang lebih besar dari pada herbal tunggalnya. Penelitian dengan menggunakan daun sirsak, daun kemangi, daun salam dan daun sirih hijau, bertujuan untuk mengetahui efektivitas ekstrak konsorsium herbal perbandingan 1:1:1:1 terhadap Pytirosporum ovale. Ekstraksi senyawa aktif menggunakan metode maserasi dan pelarut etanol 70%. Ekstrak konsorsium herbal dibuat seri konsentrasi 10, 25, 40, 55 dan 70%; kontrol negatif dan kontrol positif dengan metode difusi cakram. Data dianalisis menggunakan uji Post Hoc LSD, korelasi dan regresi linier. Hasil penelitian menunjukkan semua konsentrasi ekstrak konsorsium herbal berpotensi menghambat aktivitas jamur Pytirosporum ovale. Daerah hambat terkecil terdapat pada konsentrasi ekstrak 10% dengan diameter daerah hambat sebesar 7,33 mm sedangkan daerah hambat terbesar terjadi pada konsentrasi ekstrak 70% dengan diameter daerah hambat sebesar 15,55 mm. Diameter daerah hambat pada kontrol positif sebesar 24,66 mm. Hasil uji korelasi menunjukkan ada hubungan yang sangat erat antara konsentrasi ekstrak dengan diameter daerah hambat. Hasil uji regresi linier diperoleh nilai y=0,138x+5,889. Diameter daerah hambat jamur terpengaruhi oleh konsentrasi ekstrak sebesar 99,99% (r2=0,9999), sisanya sebesar 0,01%  oleh faktor lingkungan, Ekstrak etanol konsorsium herbal belum efektif dalam menghambat pertumbuhan jamur Pytirosporum ovale bila dibandingkan dengan kontrol positifnya.Kata kunci: Konsorsium herbal, Ekstrak etanol, Antijamur, KHM, Pytirosporum ovale